2020
DOI: 10.3892/mmr.2020.11367
|View full text |Cite
|
Sign up to set email alerts
|

miR‑204‑5p promotes apoptosis and inhibits migration of gastric cancer cells by targeting HER‑2

Abstract: Gastric cancer is one of the most common types of cancer worldwide, with a high incidence and mortality rate. MicroRNAs (miRs) play an important role in tumorigenesis, cell proliferation, migration, apoptosis and metastasis of cancer. The present study aimed to investigate the role and potential mechanism of miR-204-5p in gastric cancer. The mRNA expression levels of miR-204-5p in gastric cancer were determined by reverse transcription-quantitative PCR. Cell proliferation was determined using Cell Counting Kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…Notably, it has been documented that miR-204-5p affected the development of varied human tumors progression by regulating diverse genes such as runt-related transcription factor 2 (RUNX2) [17], human epidermal growth factor receptor 2 (HER [31], high mobility group B1 (HMGB1) [32], and RRM2 [33]. Among them, RRM2 is a catalytic subunit of ribonucleotide reductase that intensely involved in DNA synthesis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it has been documented that miR-204-5p affected the development of varied human tumors progression by regulating diverse genes such as runt-related transcription factor 2 (RUNX2) [17], human epidermal growth factor receptor 2 (HER [31], high mobility group B1 (HMGB1) [32], and RRM2 [33]. Among them, RRM2 is a catalytic subunit of ribonucleotide reductase that intensely involved in DNA synthesis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Referring to many studies, miR-204-5p was concluded as a tumor suppressor factor. For example, it has been reported that miR-204-5p attenuates tumor malignancy from various levels in gastric cancer, prostate cancer, and hepatocellular cancer [ 3 6 ]. However, some researchers observed the converse results in other tumors; for example, Zhang and his colleagues summarized a tumorigenesis role of miR-204-5p in cervical cancer [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to several studies, miRNAs are involved in the pathogenesis and development of GC, furthermore, an increasing number of miRNAs have been shown to be used as markers for diagnosis in GC treatment, and the dysregulated expression of miRNAs can remarkably affect prognosis [ 17 , 18 ]. For instance, miRNA-204-5p exerts antitumor effects by inhibiting GC cell proliferation, invasion and migration, and promoting apoptosis, suggesting that miRNA-204-5p could be a potential target for the treatment of GC [ 19 ]. Compared with other miRNAs, miRNA-381 is highly sensitive and specific in GC diagnosis.…”
Section: Discussionmentioning
confidence: 99%